A Special Report on the NHLBI Initiative to Study Cellular and Molecular Mechanisms of Arterial Stiffness and Its Association With Hypertension. Issue 11 (10th November 2017) - Oh, Young S.; Berkowitz, Dan E.; Cohen, Richard A.; Figueroa, C. Alberto; Harrison, David G.; Humphrey, Jay D.; Larson, Douglas F.; Leopold, Jane A.; Mecham, Robert P.; Ruiz-Opazo, Nelson; Santhanam, Lakshmi; Seta, Francesca; et al.
Abstract : Supplemental Digital Content is available in the text.